Comparison of collagen content in skin wounds evaluated by biochemical assay and by computer-aided histomorphometric analysis. (1st November 2016) - Caetano, Guilherme F.; Fronza, Marcio; Leite, Marcel N.; Gomes, Ary; Frade, Marco Andrey Cipriani
Abstract: Context: The quantification of total collagen is of major importance in a wide range of research areas, including the study of cutaneous wound healing and new drugs trials. Objective: The total collagen content in skin biopsies was compared by biochemical hydroxyproline assay and by two computer-aided histomorphometric analyses of histological sections. Materials and methods: Two methods were used to evaluate collagen formation: the hydroxyproline assay, as the gold standard and histomorphometric image analysis of the filled areas by corresponding stained collagen fibres, using picrosirius and Gomori's trichrome staining. The image analyses were determined by digital densitometry recognition using computer-aided ImageJ software. One-way ANOVA, simple linear regression and ANCOVA were applied for the statistical analysis and correlation. Results: In a simple linear regression analysis carried out on the 14th day period after the induction of skin injury, three techniques, picrosirius red ( F = 33.57, p = 0.00), Gomori's trichrome ( F = 81.61, p = 0.00) and hydroxyproline content ( F = 16.85, p = 0.00) were able to detect collagen production. After scale adjustment, there were no significant differences among either the slopes ( F = 1.17, p = 0.32) or the intercepts ( F = 0.69, p = 0.51) of the estimated regression lines. It seems that a highly significant correlation exists between the histomorphometrical analysis and hydroxyproline assay. Discussion and conclusion: The morphometric analysis proved to be adequate and can be used as a simple, rapid, low-cost technology for evaluating total collagen in cutaneous wound specimens, compared with the gold standard hydroxyproline assay.